2006
DOI: 10.3171/jns.2006.105.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in human glioblastoma cells produced using embryonic stem cell–derived astrocytes expressing tumor necrosis factor–related apoptosis-inducing ligand

Abstract: Engineering of transgenic hTRAIL by using ES cell-derived astrocytes induced apoptosis in human malignant glioma cells while sparing nontumor astrocytes. The apoptotic effects of transgenic hTRAIL are greater than those of recombinant hTRAIL. Analysis of these results suggests that hTRAIL-expressing-ES cell-derived astrocytes should be considered in the development of new in vivo strategies to treat malignant human gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…MSCs have been used for delivery of therapeutic cytokines like IFN-␤ (9), IL-12 (11,35), cytosine deaminase (36), and oncolytic adenovirus (37). The ability of TRAIL to selectively target tumor cells while remaining harmless to most normal cells (38)(39)(40) makes it an attractive candidate for an apoptotic therapy in highly malignant brain tumor treatment. TRAIL signals via two pro-apoptotic death receptors (DR4 and DR5), inducing a caspase-8-dependent apoptotic cascade in tumor cells (38) However, because of its short biological half-life and limited delivery across the blood-brain barrier, most promising studies using TRAIL lack applicability (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have been used for delivery of therapeutic cytokines like IFN-␤ (9), IL-12 (11,35), cytosine deaminase (36), and oncolytic adenovirus (37). The ability of TRAIL to selectively target tumor cells while remaining harmless to most normal cells (38)(39)(40) makes it an attractive candidate for an apoptotic therapy in highly malignant brain tumor treatment. TRAIL signals via two pro-apoptotic death receptors (DR4 and DR5), inducing a caspase-8-dependent apoptotic cascade in tumor cells (38) However, because of its short biological half-life and limited delivery across the blood-brain barrier, most promising studies using TRAIL lack applicability (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Since TRAIL is a membranebound protein, cell contact was necessary. 43 In this experiment, we showed that 24 hours after induction with Dox, the apoptotic rate of the human glioma cells was 58% (Fig. 4).…”
Section: Esc-derived Astrocytes Conditionally Expressing a Pro-apoptomentioning
confidence: 98%
“…In particular, diseases that shelter themselves from conventional treatments, such as chemotherapy, are in need for such therapy. Human high-grade gliomas (hHGG) are the most common primary brain tumors and remain a clinical challenge with an average life expectancy of 14 months after state of the art surgical, radiation, and chemotherapy treatments [19][20][21][22][23]. The infiltrative pattern of hHGG combined with the difficulty of chemotherapy to cross the blood-brain barrier is the main reason for treatment failure [24][25][26] and sparked interest in exploring cell-based therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell-derived astrocytes are highly desirable vectors as they have the potential for maintaining migrating capacity and, therefore, could offer advantages over other delivery vectors in the treatment of brain tumors. We have published that mouse ESC (mESC)-derived astrocytes can be successfully used as cell-based gene therapy for treatment of experimental HGG [23,28]. To translate these results to the clinical setting, patient-specific iPSC derived without viral vectors, that is, ''footprint-free'', are needed.…”
Section: Introductionmentioning
confidence: 99%